Anxiety Levels Of Nurse Profession Students During The Covid-19 Pandemic During Nursing Practices At Santa Elisabeth Hospital Medan In 2021 - Fenny Angelina Purba (Jurnal EduHealth, 2022)
Background: Anxiety is an emotional condition with a feeling of discomfort in a person, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that is not yet clear. The results showed that the level of anxiety was categorized as mild as many as 36 respondents (42.9%), in the moderate category as many as 47 respondents (56%), in the severe category as many as 1 respondent (1.2%) Methods: The research design was a descriptive design with the Cross design method. sectional. Sampling technique with total sampling technique with a total sample of 84 people Results: The results showed that the level of anxiety was categorized as mild as many as 36 respondents (42.9%), in the moderate category as many as 47 respondents (56%), in the severe category as many as 1 respondent (1 ,2%). Discussion.